The Region of Difference Four is a Robust Genetic Marker for Subtyping Mycobacterium caprae Isolates and is Linked to Spatial Distribution of Three Subtypes. Issue 3 (31st October 2015) - Rettinger, A.; Broeckl, S.; Fink, M.; Prodinger, W. M.; Blum, H.; Krebs, S.; Domogalla, J.; Just, F.; Gellert, S.; Straubinger, R. K.; Büttner, M.
Summary: Alpine Mycobacterium caprae isolates found in cattle and red deer display at least three genetic variations in the region of difference four (RD4) that can be used for further differentiation of the isolates into the subtypes 'Allgäu', 'Karwendel' and 'Lechtal'. Each genomic subtype is thereby characterized by a specific nucleotide deletion pattern in the 12.7‐kb RD4 region. Even though M. caprae infections are frequently documented in cattle and red deer, little is known about the transmission routes. Hence, robust markers for M. caprae subtyping are needed to gain insight into the molecular epidemiology. For this reason, a rapid and robust multiplex PCR was developed for the simultaneous detection of three M. caprae RD4 subtypes and was used to subtype a total number of 241 M. caprae isolates from animals (145 cattle, 95 red deer and one fox) from Bavaria and Austria. All three subtypes occur spatially distributed and are found in cattle and in red deer suggesting transmission between the two species. As subtypes are genetically stable in both species it is hypothesized that the described genetic variations developed within the host due to 'within‐host replication'. The results of this study recommend the genomic RD4 region as a reliable diagnostic marker for M. caprae subtype differentiation.